Neuronal Migration Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Thirty patients with intractable partial epilepsy and a pathological or radiological diagnosis of neuronal migration disorders (NMD) were studied at the Montreal Neurological Institute and Hospital, Montreal, Quebec, Canada.